Dampak Aplikasi Pestisida Sipermetrin, Deltametrin, Klorpirifos dan λ-Sihalotrin Terhadap Kandungan Residu Pestisida pada Biji Kakao - Bayu Refindra Fitriadi; Ayutia Ciptaningtyas Putri (Jurnal AGROSAINS dan TEKNOLOGI, 2019)
The use of various types of active ingredients with high intensity pesticides in dealing with pest disturbances often makes farmers pay less attention to the negative impacts. Deltamethrin, sipermetrin, λ-cyhalothrin and chlorpyrifos are active ingredients of pesticides that are often used by cocoa farmers to control pests Helopeltis sp. spp. which is one of the main pests in cocoa plants. Field tests on pesticide application were carried out on cocoa plants with Helopeltis sp. spp. High. This test was carried out on 4 treatment blocks applied with different active ingredients. Pesticide residue testing was carried out on cocoa beans, before and after pesticide application using the QuEChERS method on GC-ECD. The results of pesticide residue testing showed that the use of λ-cyhalothrin pesticides did not leave pesticide residues, while sipermetrin pesticides left far fewer pesticide residues compared to deltamethrin and chlorpyrifos pesticides. The results of these pesticide residues are compared to the Pesticide Maximum Residual Limit (MRL) according to the European Commission Part A of Annex I to Reg. 396/2005, shows the results of λ-cyhalothrin and cipermethrin pesticide residues test under pesticide MRL, while the results of deltamethrin and chlorpyrifos pesticide residue test are above the specified pesticide MRL.